The Effectiveness of Traffic Public Education in Preventing Traffic Accidents in The Payakumbuh Police Office - Zainal Azis (Advances in Police Science Research Journal, 2021)
Traffic accidents are one of the problems in the field of traffic that road users in Indonesia are wary of. This study portrays how traffic accidents occur in the Payakumbuh Police Office jurisdiction. The purpose is to describe the effectiveness of Traffic Public Education in preventing traffic accidents in the Payakumbuh Police Office jurisdiction. Efforts to prevent traffic accidents have been carried out with the hope that traffic accidents will decrease from the previous year. Traffic Public Education is a preventive operational activity to increase public awareness in traffic so that the risk of traffic accidents can be reduced. The implementation of Traffic Public Education is carried out in accordance with the Implementation Instructions of the National Police Chief No. Pol: Juklak/05/V/2003. As an analytical tool to discuss this research, George R Terry's management theory and effectiveness theory are used with a qualitative approach. Data collection was performed through interview, observation and document review techniques. Meanwhile, data analysis was executed with data reduction, data presentation, and drawing conclusions. Based on the study's result discussion, it can be concluded that the activities of Traffic Public Education still need improvement in terms of resources, processes and goals or targets to be achieved. The factors influencing the implementation of Traffic Public Education at the Payakumbuh Police Office include internal and external factors. The internal factors are related to human resources, facilities, and infrastructure, while external factors include the condition of the people in Payakumbuh City.